Efforts to Increase the Professionalism of The General Election Commission (Kpu) Of Pati District in Organizing The 2024 Regional Elections - Septiana, Lisa; Addiansyah, M.Nur Rofiq (LEGAL BRIEF, 2024)
This article will show how efforts to improve the professionalism of the Pati Regency KPU in organizing the 2024 Pilkada. This professionalism can be seen from the technical guidance (bimtek) for implementers and updating of voter data and monitoring activities, political education and socialization of the election to voters, provision of facilities and infrastructure, legality to candidates, and socialization of the neutrality of ASN and village heads in the 2024 Pati Regency Pilkada, as well as the integrity value of the Pati Regency KPU. We can see this from the community who dare to channel their opinions (aspirations) to government institutions (the Pati Regency KPU) which are used as a form of support or input for the future so as to produce democratic public policies (in accordance with the needs of the community). One of the objectives of this article is to see how efforts to improve the professionalism of the Pati Regency KPU in carrying out its responsibilities, especially approaching the election year, such as the quality of the services provided, whether they are effective and accurate according to the guidelines of the Central KPU. Meanwhile, this research method uses a qualitative method with a descriptive approach type, interviews, and documentation at the Pati Regency KPU which is supported by online reference searches such as journals, E-books, papers, and the like. The results/findings of this research indicate that efforts to improve the professionalism of the Pati Regency KPU in organizing the 2024 Pilkada are able to provide performance wholeheartedly and accurate information that is poured out directly or indirectly so that it is hoped that public participation in the 2024 Pilkada can increase. Through this professionalism, the public is expected to give their voting rights according to applicable procedures so that it can help increase public trust in the performance of the Pati Regency KPU which will then be an improvement in the upcoming election. Therefore, the implications of this research if not carried out will have a negative impact on certain aspects, including the low level of supervision and evaluation of the performance of the Pati Regency KPU so that it will potentially lead to a decrease in the professionalism of the KPU itself which will have an impact on public trust being lost, considering that through public trust it can help to ensure justice and legitimacy in the election process. It is different if the implications of this research are carried out in order to prevent abstention behavior and public apathy and to ensure that the implementation of the regional elections runs according to applicable principles. Therefore, without this research, the risk of problems occurring in the implementation of elections will increase